The Long Non-coding RNA LINC01705 Regulates the Development of Breast Cancer by Sponging miR-186-5p to Mediate TPR Expression as a Competitive Endogenous RNA - Du, Chuang; Zhang, Jun-ling; Wang, Yan; Zhang, Ying-ying; Zhang, Jian-hua; Zhang, Lin-feng; Li, Jing-ruo (Frontiers in Genetics, 2020)
Long non-coding RNAs (lncRNAs) may be a regulatory factor of tumorigenesis. However, it is unclear what its biomechanisms are in breast cancer. In this study, different lncRNAs were detected in breast cancer through microarray analysis (GSE119233) and LINC01705 was selected for further study. qRT-PCR was then utilized for the detection of LINC01705 expression in breast cancer cells. A transwell assay, flow cytometry, 5-ethynyl-2’-deoxyuridine (EdU), a cell counting Kit-8 (CCK-8), and a wound-healing assay were performed to determine cell migration, invasion, apoptosis, and proliferation in breast cancer, respectively. For the identification of potential targets of LINC01705, dual-luciferase reporter gene and bioinformatics assays were conducted. Moreover, for the clarification of their interaction and roles in the regulation of the occurrence of breast cancer, Western blotting and RIP assays were conducted. Our findings revealed high LINC01705 expression in breast cancer tissues relative to adjacent non-cancerous tissues (n=40, P<0.001). Overexpression of LINC01705 notably enhanced cell migration and proliferation in breast cancer. In addition, LINC01705 positively regulated the translocated promoter region, nuclear basket protein (TPR) through competition with miR-186-5p. In conclusion, our results suggest that LINC01705 is implicated in the progression of breast cancer via competitively binding to miR-186-5p as a competing endogenous RNA (ceRNA), thereby regulating TPR expression.